Comprehensive Analysis of the Transcriptome-Wide m6A Methylome in Pterygium by MeRIP Sequencing - Jiang, Yaping; Zhang, Xin; Zhang, Xiaoyan; Zhao, Kun; Zhang, Jing; Yang, Chuanxi; Chen, Yihui (Frontiers in Cell and Developmental Biology, 2021)
Aim: Pterygium is a common ocular surface disease, which is affected by a variety of factors. Invasion of the cornea can cause severe vision loss. N6-methyladenosine (m6A) is a common post-transcriptional modification of eukaryotic mRNA, which can regulate mRNA splicing, stability, nuclear transport, and translation. To our best knowledge, there is no current research on the mechanism of m6A in pterygium. Methods: We recruited 24 pterygium patients from Shanghai Yangpu Hospital, and the level of m6A modification was detected using an m6A RNA Methylation Quantification Kit. Expression and location of METTL3, a key m6A methyltransferase, were identified by immunostaining. Then we used m6A-modified RNA immunoprecipitation sequencing (MeRIP-seq), RNA sequencing (RNA-seq) and bioinformatics analyses to compare the differential expression of m6A methylation in pterygium and normal conjunctival tissue. Results: We identified 2949 dysregulated m6A peaks in pterygium tissue, of which 2145 were significantly upregulated and 804 were significantly downregulated. The altered m6A peak of genes were found to play a key role in the Hippo signaling pathway and endocytosis. Joint analyses of MeRIP-seq and RNA-seq data identified 72 hypermethylated m6A peaks and 15 hypomethylated m6A peaks in mRNA. After analyzing the differentially methylated m6A peaks and synchronously differentially expressed genes, we searched the Gene Expression Omnibus database and identified five genes related to the development of pterygium (DSP, MXRA5, ARHGAP35, TMEM43, and OLFML2A). Conclusion: Our research shows that m6A modification plays an important role in the development of pterygium and can be used as a potential new target for the treatment of pterygium in the future.